Rashtriya swayamsewak sangh - "Goyal, D.R" (New Delhi, 1979)
The author acknowledges with gratitude the help and encouragement of the Quami Ekta Trust, its chairman Smt. Subhadra Joshi and other trustees who provided the wherewhithal for elaborate and detailed study of an organisation which has hitherto been treated as an esoteric club.
Keywords: Rashtriya Swayamsewak Sangh